The Coincidence of Familial Mediterranean Fever and Hypereosinophilia in a Patient with Hereditary Elliptocytosis - Keklik, Muzaffer (Springer India, 2013)
Familial Mediterranean fever (FMF) is a genetic disease with autosomal inheritance characterized by recurrent fever, abdominal pain, and serositis attacks. It is relatively common in the races and ethnical groups around Mediterranean Sea (Sephardic Jews, Armenians, Turks and Arabians). Hereditary elliptocytosis (HE) is common genetic defect of the red blood cell membrane skeleton. Spectrin mutations are the predominant causes of HE. Hypereosinophilia is defined as a number of eosinophil granulocytes equal or greater than 0.5 × 10(9)/L of circulating blood. The main causes are allergies and parasitic infections. This case report describes a Turkish female HE patient who presented with FMF and hypereosinophilia. Genetic analysis revealed heterozygous mutation in exon 10 of the MEFV gene (V726A). The patient was successfully treated with colchicine and steroid treatment at 3-month follow-up. To the best of our knowledge, this is the first report of association between FMF, HE, and hypereosinophilia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12288-013-0296-6) contains supplementary material, which is available to authorized users.